Vela Pećina near Kali (In situ, 2024)
Trial excavations of Vela Pećina (big cave) near Kali on the island of Ugljan have confirmed the archaeological potential of the site. The cultural layers were documented up to a relative depth of 1.2 m, that is to the bedrock. The inventory of finds consisted mostly of knapped stone and animal bone items. Based on a preliminary examination, first of all the lithic assemblage, the lower part of the stratigraphic sequence can be dated to the Late Glacial period in strictly chronological terms, i.e. the Late Epigravettian in cultural-chronological terms.
Keywords: Vela Pećina; Kali; Ugljan; Epigravettian; Upper Palaeolithic